The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/1010428317703655
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-200c plays an oncogenic role in nasopharyngeal carcinoma by targeting PTEN

Abstract: Recent studies suggested that microRNA-200 family microRNAs play critical roles in cancer initiation and metastasis. The underlying mechanism remained elusive. In this study, we show that microRNA-200c is upregulated in nasopharyngeal carcinoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…It has been reported that PTEN was a direct target of miR-200b and miR-200c in endometrial cancer and nasopharyngeal carcinoma [28, 29]. In addition, a growing number of studies indicated that PTEN played an important role in the abnormal proliferation of PCOS GCs [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PTEN was a direct target of miR-200b and miR-200c in endometrial cancer and nasopharyngeal carcinoma [28, 29]. In addition, a growing number of studies indicated that PTEN played an important role in the abnormal proliferation of PCOS GCs [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…PTEN is a well-characterized tumor suppressor gene, which antagonizes the phosphoinositol-3-kinase/protein kinase B (PKB or Akt) signaling pathway [ 12 ]. The PTEN gene acts as a tumor suppressor gene in multiple cancers, including breast cancer [ 13 , 14 ], nasopharyngeal carcinoma [ 15 ], renal cell carcinoma [ 16 ], non-small-cell lung cancer [ 17 ], hepatocellular carcinoma [ 18 ], human NK/T-cell lymphoma [ 19 ], and osteosarcoma [ 20 ]. The loss of function of PTEN in tumor cells results in the accumulation of critical cell messengers, which increases Akt phosphorylation and activity and leads to decreased apoptosis and/or increased mitogenic signaling [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“… 12 Notably, miRNAs were reported to regulate EMT in a number of studies. For example, the miR-200 family was shown to directly target Nanog to inhibit EMT, but may play an oncogenic role in NPC, 13 , 14 whereas miR-30 was shown to target Snail1 to inhibit invasion and metastasis in the regulation of EMT. 15 …”
Section: Introductionmentioning
confidence: 99%